Beyond the creative industries. (1st October 2013) - MacDonald, Stuart
Although Creative Industries as engines of post-industrial economies have assumed an increasing global priority with implications for art education at all levels few studies exist. Nomenclature here is contested, especially when arts' role appears freighted with alien concepts of industry and commerce. But much of this debate concerns visual and performing arts, only part of a larger cluster comprising, amongst others, architecture, design, fashion and games. And, Creative Industries are now seen as important socially as economically. This article takes classification as least problematic, concentrating instead on people working in the Creative Industries (largely in Glasgow and Scotland), their interactions and networking within a creative ecology, and real-world interactions with education. It presents examples of collaboration, co-creativity and co-design, and cross-disciplinarity, arguing for a strategic role for design and design thinking linked to social and economic innovation, where educational gains are prime, and revisiting earlier debates about postmodern art education.